Village Information System (SID) Effectiveness in Improving Village Administrative Services: Efektivitas Sistem Informasi Desa (SID) Dalam Meningkatkan Pelayanan Administrasi Desa - Novianti, Rosita Dwi; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2024)
This research investigates the effectiveness of the Village Information System (SID) in improving public services in Sekardangan Village, focusing on the period of 2020-2022. The descriptive qualitative method is employed, utilizing primary and secondary qualitative data sources, including library research and interviews with the village head and operators. Results reveal that Sekardangan Village provides effective, fast, precise, and efficient services. However, the web-based SID has not been fully effective due to challenges faced by elderly residents with limited socialization from local government. This study contributes to the understanding of smart governance and the role of information systems in enhancing village administration services. Highlight : The study analyzes the effectiveness of the Village Information System (SID) in improving public services in Sekardangan Village, focusing on the period of 2020-2022. Qualitative data sources, including library research and interviews with the village head and operators, were utilized to assess the effectiveness of the SID. The results indicate that while Sekardangan Village provides effective, fast, precise, and efficient services, the web-based SID has not been fully effective due to challenges faced by elderly residents with limited socialization from the local government. Keywords: Effectiveness, Village Information System, Public Service, Sekardangan Village, Qualitative Method